Implementation of the Law in Confirming the Boundary between Nagari Koto Kaciak and Nagari Duo Koto in Agam Regency - Ahda Syukri; Edi Haskar; Nessa Fajriyana Farda (Civiliza Publishing, 2026)
National refugee children are a vulnerable group who often face obstacles in accessing education, even though this right is guaranteed in various regulations. This study aims to determine national legal regulations regarding the right to education for refugee children and the role of the Regional Immigration Office in ensuring it. This research method is descriptive analytical with a sociological juridical approach. The results show that although several regulations guarantee the right to education in general, there are no technical provisions that specifically regulate the rights of refugee children. The East Java Regional Immigration Office acts as a coordination facilitator, but still faces challenges such as limited documentation, lack of policy synchronization, and lack of understanding of technical implementers. Affirmative policies and national technical guidelines are needed, as well as strengthened cross-sectoral coordination so that children's right to education can be fulfilled fairly and inclusively.